A identidade do sujeito analfabeto em contradição na mídia - Inhoti, Aline Almeida (2011)
This research has as its theme and objective the establishment of identity of the illiterate subject by Época magazine, 2010. By observing that, in contemporary society, the media circulates discourses that deal with public policies for social inclusion of the subject illiterate, this work seeks to demonstrate how the magazine Época, 2010, by the exercise of biopower (de)constructs the identity of the subject illiterate Brazilian. Because of the media composing places of demonstrations of knowledge and powers that enable to mobilize the creation of the contemporary subject, it casts itself as surface emergency statements, statements that are subject to what can and what should be said in the irruption of their appearance. Our movement theoretical and analytical framework is based on Discourse Analysis of the French line, specifically in the studies of Michel Foucault. Appealed also to cultural studies to understand the constitution of identities in contemporary history and the processes of education and literacy, illiteracy, literacy, functional literacy in our society. The methodological frameworks are driven by key concepts: normalization, biopower, biopolitics, discipline, knowledge, power, truth, contradiction, file, function and expository statement. This theoretical approach has allowed us to build an archive of material broadcast media in 1971, 2003, 2009 and 2010, being presented as: a) print b) television media and c) film media. In the quest for verticality of the associated field, we observed that the discursive practices conflict erupted in the media point of view and conceive the subject illiterate. This contradiction is concentrated mainly in the legislative field, in science and in the political/social. The discourse mine in the contradiction which establishes a set of (re)signification in the subjectivity of the subject illiterate, visible in discursive media. In the last century these are governed by two sets of operating mechanisms of biopower, biopolitics and disciplines. In these procedures, we used the expectation of this work contribute to the performance of teachers, especially professionals of literature, pedagogy and literacy, as guiding paths that deconstruct evidence senses put in the history of education. Nevertheless, we also hope to collaborate on improving the practice of reading imagery, to instigate the production professionals to make use visual teaching in schools.